2019
DOI: 10.1111/sltb.12608
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Investigation of the Interaction Between Social Problems and Neuropsychological Characteristics on the Development of Suicide Ideation

Abstract: Objective Negative social interactions are known to contribute to the development of suicide ideation. However, it is unclear how this risk factor interacts with other predisposing risk factors. The purpose of this study was to determine how social and neuropsychological factors interact as a prospective predictor of the emergence of suicide ideation in adolescents. Method Data were collected from adolescents (M age = 13.12, SD = 1.48) over 3 years as part of a larger study. Participants completed the MINI‐Kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Students who were from urban, senior high school students, boarding students, and whose parents’ educational level above high school degree, and those with fewer friends and lower family economy condition were likely to experience different suicidal behaviors. Taken together, the causes of suicidal behaviors were associated with multiple social ecological conditions, including biological, cognitive factors, school, and family [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students who were from urban, senior high school students, boarding students, and whose parents’ educational level above high school degree, and those with fewer friends and lower family economy condition were likely to experience different suicidal behaviors. Taken together, the causes of suicidal behaviors were associated with multiple social ecological conditions, including biological, cognitive factors, school, and family [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one cross-sectional study found that WCST-PE scores were not significantly associated with current SI severity among veterans (Homaifar et al, 2016), whereas another research team found worse WCST-PE performance in depressed participants with (vs. without) current SI (Marzuk et al, 2005). In contrast, longitudinal studies report that poorer WCST-PE performance may predict more severe SI 6 months to 3 years later among undergraduate students (Miranda et al, 2012, 2013), but fail to predict SI severity in adolescents at the 1-year follow-up (McManimen & Wong, 2020). Nonetheless, poorer performance on WCST-PE may indicate general cognitive inflexibility that, when combined with other established risk factors (e.g., hopelessness), increases SI risk among undergraduates.…”
Section: Resultsmentioning
confidence: 93%
“…CWIT-4. Two studies reported that worse CWIT-4 performance predicted a greater likelihood of future SI occurrence and severity (Kasckow et al, 2016;McManimen & Wong, 2020). However, CWIT-4 performance in the absence of negative life events may have limited predictive utility.…”
Section: Stroop Testmentioning
confidence: 99%
“…McManimen and Wong ( 2020 ) conducted a study to analyze the interaction of three aspects of executive functions that may have an impact on SI: cognitive flexibility, task switching, and distractibility. Cognitive rigidity has been associated with multiple adverse mental health problems, including SI (Novak et al, 2022 ).…”
Section: Cognitive Flexibility Passive Suicidal Ideation Depression A...mentioning
confidence: 99%
“…The risk factors that influence suicidal ideation are diverse, yet little has been achieved in the effective prediction of suicide (Fazakas-DeHoog et al, 2017 ; McManimen and Wong, 2020 ; MacPherson et al, 2022b ). Recent studies have shown that patients with suicidal ideation (SI) or suicide attempt (SA) are referred to hospitals for treatment with drugs such as ketamine or clozapine as the only rehabilitation option.…”
Section: Introductionmentioning
confidence: 99%